Mild cold induced thermogenesis: are BAT and skeletal muscle synergistic partners?. Issue 5 (28th September 2017) - Bal, Naresh C.; Maurya, Santosh K.; Pani, Sunil; Sethy, Chinmayee; Banerjee, Ananya; Das, Sarita; Patnaik, Srinivas; Kundu, Chanakya N.
Abstract : There are two well-described thermogenic sites; brown adipose tissue (BAT) and skeletal muscle, which utilize distinct mechanisms of heat production. In BAT, mitochondrial metabolism is the molecular basis of heat generation, while it serves only a secondary role in supplying energy for thermogenesis in muscle. Here, we wanted to document changes in mitochondrial ultrastructure in these two tissue types based upon adaptation to mild (16°C) and severe (4°C) cold in mice. When reared at thermoneutrality (29°C), mitochondria in both tissues were loosely packed with irregular cristae. Interestingly, adaptation to even mild cold initiated ultrastructural remodeling of mitochondria including acquisition of more elaborate cristae structure in both thermogenic sites. The shape of mitochondria in the BAT remained mostly circular, whereas the intermyofibrilar mitochondria in the skeletal muscle became more elongated and tubular. The most dramatic remodeling of mitochondrial architecture was observed upon adaptation to severe cold. In addition, we report cold-induced alteration in levels of humoral factors: fibroblast growth factor 21 (FGF21), IL1α, peptide YY (PYY), tumor necrosis factor α (TNFα), and interleukin 6 (IL6) were all induced whereas both insulin and leptin were down-regulated. In summary, adaptation to cold leads to enhanced cristae formation in mitochondria in skeletal muscle as well as the BAT. Further, the present study indicates that circulating cytokines might play an important role in the synergistic recruitment of the thermogenic program including cross-talk between muscle and BAT.